THE RELATIONSHIP OF SOCIO- ECONOMIC STATUS AND THE OCCURRENCE INJURY OF DIABETES MELLITUS PATIENTS - Mayawati, Desti; Kamal, Sodiq; Wahyuningtyas, Eka Sakti (Universitas Respati Yogyakarta, 2021)
Socio-economic status includes a person's lack of education and income which can affect a person's health status. The purpose of this study was to determine whether there is a relationship between socioeconomic status and the incidence of injury in people with Diabetes Mellitus. The method used is a correlation analytic design, with a cross-sectional approach with a sample of 120 respondents. The instrument used was a questionnaire. The data were processed using the Spearman statistical test. The results showed that there was a significant relationship between socioeconomic status and the incidence of injury (p-value = 0.001; r = -0.313). Results of multivariate analysis in research using linear regression that shows that the R result is 0.343. The socioeconomic status regression coefficient on the incidence of injury was 0.185 while the regression coefficient for self-care activities on the incidence of injury was 0.133. A socio-economic status that includes education and income influences a person to carry out self-care management to prevent complications of Diabetes Mellitus, namely Diabetic ulcer. Keywords: Diabetes Mellitus; Incident Of Injury; Socio-Economic Status